The function of Mn2+ additive in aqueous electrolyte for Zn/δ-MnO2 battery. (10th August 2020) - Qiu, Ce; Zhu, Xiaohui; Xue, Liang; Ni, Mingzhu; Zhao, Yang; Liu, Bo; Xia, Hui
Abstract: Adding Mn 2+ in aqueous electrolyte is a well adopted approach to improve cycle performance for Zn/MnO2 batteries. The function of Mn 2+ additive in aqueous electrolyte, however, is not well understood, which could affect revealing the real performance of the MnO2 cathode itself. In this work, a battery system with Zn anode and birnessite MnO2 cathode is constructed and systematically investigated by using MnSO4 additive in the electrolyte with different concentrations. The function of Mn 2+ in the electrolyte, the structural evolution of the electrode, the reaction mechanism, and the cause for capacity fading are comprehensively investigated in this system. It is found that Mn 2+ can be continuously electro-oxidized at the cathode and form ε-MnO2 when the charge voltage is above 1.7 V during cycling, leading to successive capacity increase up to hundreds of cycles. The capacity increase, however, stops after certain cycle numbers, and is followed by fast capacity fading, which is correlated to the competition between ε-MnO2 formation and phase transition from birnessite to spinel ZnMn2 O4 . It is suggested that addition of Mn 2+ in the electrolyte cannot stabilize the MnO2 cathode and the improved cycle performance is achieved at the expense of consuming the Mn 2+ in the electrolyte. Graphical abstract: Image 1 Highlights: The function of Mn 2+ is investigated in a aqueous Zn/δ-MnO2 (birnessite) system. The cycle performance is highly dependent on voltage window and Mn 2+ concentration. Mn 2+ additive can conceal the real performance of MnO2 due to electro-oxidation. Mn dissolution may not be the main reason causing fast capacity fading for MnO2 . The reaction mechanism and cathode structure evolution of Zn/δ-MnO2 are investigated.